Influence of the Belgian Coast on Well-Being During the COVID-19 Pandemic. Issue 1 (20th September 2021) - Severin, Marine I.; Vandegehuchte, Michiel B.; Hooyberg, Alexander; Buysse, Ann; Raes, Filip; Everaert, Gert
There is increasing evidence that blue spaces, particularly coastal environments, are beneficial for well-being. During the first-wave lockdown of the COVID-19 pandemic in Belgium, access to the coast was restricted due to restraint in circulation. Making use of this unique opportunity, this study investigated whether access and visits to the coast were positively associated with well-being by using a quasi-experimental design. The emotions of awe and nostalgia were studied as potential mediators between coastal visits and well-being. A total of 687 Flemish adults took part in an online survey that was launched end of April until beginning of June 2020. After controlling for covariates, results showed that access to the coast, but not visit frequency, was positively associated with well-being. More specifically, coastal residents reported less boredom and worry, and more happiness than inland residents. Awe and nostalgia were not significantly associated with coastal visits, but awe was negatively correlated with boredom. The study suggests a potential buffer effect of residential proximity to the coast against negative psychological consequences of the COVID-19 pandemic, supporting the notion that the coast has a positive impact on well-being.